What makes online substance-use interventions engaging? A systematic review and narrative synthesis - Joanna Milward; Colin Drummond; Stephanie Fincham-Campbell; Paolo Deluca (Digital Health, 2018)
Background Online substance-use interventions are effective in producing reductions in harmful-use. However, low user engagement rates with online interventions reduces overall effectiveness of interventions. Identifying optimal strategies with which to engage users with online substance-use interventions may improve usage rates and subsequent effectiveness. Objectives (1) To identify the most prevalent engagement promoting strategies utilised to increase use of online substance-use interventions. (2) To determine whether the identified engagement promoting strategies increased said use of online substance-use interventions. Review methods The reviewed followed Cochrane methodology. Databases were searched for online substance-use interventions and engagement promoting strategies limited by study type (randomised controlled trial). Due to heterogeneity between engagement promoting strategies and engagement outcomes, meta-analytic techniques were not possible. Narrative synthesis methods were used. Results Fifteen studies were included. Five different engagement promoting strategies were identified: (1) tailoring; (2) delivery strategies; (3) incentives; (4) reminders; (5) social support. The most frequently reported engagement promoting strategies was tailoring (47% of studies), followed by reminders and social support (40% of studies) and delivery strategies (33% of studies). The narrative synthesis demonstrated that tailoring, multimedia delivery of content and reminders are potential techniques for promoting engagement. The evidence for social support was inconclusive and negative for incentives. Conclusions This review was the first to examine engagement promoting strategies in solely online substance-use interventions. Three strategies were identified that may be integral in promoting engagement with online substance-use interventions. However, the small number of eligible extracted studies, inconsistent reporting of engagement outcomes and diversity of engagement features prevent firmer conclusions. More high-quality trials examining engagement are required.